A conceptual framework for understanding the social acceptance of energy infrastructure: Insights from energy storage. (August 2017) - Devine-Wright, Patrick; Batel, Susana; Aas, Oystein; Sovacool, Benjamin; Labelle, Michael Carnegie; Ruud, Audun
Abstract: Although social acceptance research has blossomed over the last decade, interdisciplinary studies combining market, socio-political and community aspects are scarce. We propose a novel integration of social science theory in which the belief systems or social representations held by key actors play a crucial role in fostering acceptance of novel technologies, and where a polycentric perspective places particular emphasis on ways that middle actors mediate processes of change between scales. We advance a methodological approach that combines qualitative and quantitative research methods and exemplify the framework by focusing on acceptance of renewable energy storage solutions to accommodate high levels of renewable energy deployment. A research agenda for the social acceptance of energy storage is proposed that sets out key research questions relating international, national and local levels. The outcome of such studies would not only lead to enhanced understanding of processes of social acceptance, but deliver important insights for policy and practice. Highlights: Social acceptance studies rarely combine market, socio-political & community issues. We propose a novel framework emphasising belief systems and polycentric actors. We exemplify the framework focussing on acceptance of energy storage solutions. A research agenda is proposed that sets out key research questions.